2021
DOI: 10.1126/sciadv.abg7653
|View full text |Cite
|
Sign up to set email alerts
|

Order from disorder in the sarcomere: FATZ forms a fuzzy but tight complex and phase-separated condensates with α-actinin

Abstract: In sarcomeres, α-actinin cross-links actin filaments and anchors them to the Z-disk. FATZ (filamin-, α-actinin-, and telethonin-binding protein of the Z-disk) proteins interact with α-actinin and other core Z-disk proteins, contributing to myofibril assembly and maintenance. Here, we report the first structure and its cellular validation of α-actinin-2 in complex with a Z-disk partner, FATZ-1, which is best described as a conformational ensemble. We show that FATZ-1 forms a tight fuzzy complex with α-actinin-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 154 publications
2
30
0
Order By: Relevance
“…In addition, cardiomyocytes were striated with well-organized Z-lines (marked by α-Actinin in Fig. 5 F and G), suggesting that the fabricated cardiac tissue had developed and maintained intact myofibril structures, which is the physiological basic for heart contraction [ 18 , 19 ]. Cardiac differentiation from hESCs in the bioreactor also generated VE-Cadherin + endothelial cells, which were deeply buried inside the cardiac muscles ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cardiomyocytes were striated with well-organized Z-lines (marked by α-Actinin in Fig. 5 F and G), suggesting that the fabricated cardiac tissue had developed and maintained intact myofibril structures, which is the physiological basic for heart contraction [ 18 , 19 ]. Cardiac differentiation from hESCs in the bioreactor also generated VE-Cadherin + endothelial cells, which were deeply buried inside the cardiac muscles ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MYOZ1 was identified as one of the calcineurin-interacting proteins (calsarcins), functioning to harness calcineurin to α-actinin at the Z-line [ 29 ]. A recent structural study [ 27 ] found that MYOZ1 (FATZ1) has multiple binding sites for other sarcomere proteins, creating an interaction hub for Z-line proteins [ 27 ]. For example, MYOZ1 binds to α-actinin-2/-3, myotilin, and filamin-C through its C-terminal region [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our yeast 2-hybrid (Y2H) screening identified Myozenin1 (MYOZ1; calsarcin-2) as a potential FBXL21 binding protein. MYOZ1 is a core Z-disc protein [27], believed to serve as a scaffold containing multiple binding sites for various sarcomere partners like α-actinin and TCAP to regulate skeletal muscle structure and function [27]. Importantly, MYOZ1 has been demonstrated to inhibit calcineurin-NFAT signaling by binding and sequestering calcineurin to Z-line, blocking NFAT nuclear translocation and transcriptional activation of target genes [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial protein configuration was taken from the FReD X‐ray structure with R406C and P456L variants introduced using PyMOL (Schrodinger, 2015). The structures were subjected to all‐atom molecular dynamic (MD) simulations in the microsecond range using GROMACS 5.1.4 (Abraham et al , 2015) and Amber99SB‐ILDN force field (Lindorff‐Larsen et al , 2010) as described previously (Sponga et al , 2021), with the following differences: box‐size = 6 × 6 × 6 nm 3 , TIP3P water (Jorgensen, 1981) and no position restraints during production run. Root‐mean‐squared deviations (RMSD) from the starting configuration were calculated over backbone atoms (GROMACS rms utility).…”
Section: Methodsmentioning
confidence: 99%